Wrinkle-free graphene electrodes in zinc tin oxide thin-film transistors for large area applications. (17th January 2017) - Lee, Se-Hee; Kim, Jae-Hee; Park, Byeong-Ju; Park, Jozeph; Kim, Hyun-Suk; Yoon, Soon-Gil
Abstract: Wrinkle-free graphene was used to form the source–drain electrodes in thin film transistors based on a zinc tin oxide (ZTO) semiconductor. A 10 nm thick titanium adhesion layer was applied prior to transferring a conductive graphene film on top of it by chemical detachment. The formation of an interlayer oxide between titanium and graphene allows the achievement of uniform surface roughness over the entire substrate area. The resulting devices were thermally treated in ambient air, and a substantial decrease in field effect mobility is observed with increasing annealing temperature. The increase in electrical resistivity of the graphene film at higher annealing temperatures may have some influence, however the growth of the oxide interlayer at the ZTO/Ti boundary is suggested to be most influential, thereby inducing relatively high contact resistance.